Optimizing Encorafenib Validation: A Quality by Design Approach Empowered by Green Chemistry - Jena, Diptimayee; Jabeen, Asra; Mahato, Akash Deep; Choudhary, Khush; Mahato, Roshan; Chakraborty, Pakhi; Mishra, Kirtimaya (International Journal of Pharmaceutical Investigation, 2025)
Background Green chemistry, also known as environmentally sustainable chemistry, is an area of study within a field of chemistry with the main goal of reducing the negative effects associated with chemical reactions and outcomes. Main aim is for fostering development of environmentally conscious as well as sustainable therapies by reducing/eliminating the employment of harmful chemical substances, limiting creation of dangerous substances and conserving energy and resources. Materials and Methods In this investigation, linearity was observed for Encorafenib (ENFB) at concentrations ranging from 2 to 12 μg/mL. The technique of solving simultaneous equations was applied in order to determine the drug concentrations. Results and Discussion The estimated recovery percentage from the chosen dosage form, capsules, with a sample size of six, was 100.4% with a Standard Deviation of ±0.028 (SD). The recovery rates of accuracy study, on average, fell between 99.8 and 101.05%. Throughout intra-day assessments, the observed percentage relative standard deviation, or %RSD, was continuously less than 2%, demonstrating a high level of accuracy in this recommended methodology. The outcome of validation process and the statistical analysis of these recommended methodologies show that the suggested processes can be implemented in the stimulated quality control laboratories. Conclusion The current method is regarded to be adequate for evaluating ENFB in capsule dosage formulation quantitatively since it successfully eradicates any possible interference from regularly used excipients. As a result, such procedure is applicable to a wide range of analytical purposes.
Keywords: Drug concentrations; Encorafenib; Green Chemistry; Quality by design; Statistical analysis; Validation